SKALA PENGUKURAN DAN TEKNIK SAMPLING - Amirullah Husin; Mona Vebyani; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to resynthesize crucial concepts regarding measurement scales and sampling techniques to address methodological discrepancies that frequently occur in educational research. In the dynamics of educational management, the accuracy of the variable quantification process and the representativeness of the sample are the primary determinants of the validity of empirical findings and the accuracy of generalizations of research results. The method used in this article is a library research study with a qualitative-descriptive approach, which examines relevant scientific literature from the last five years. The results of the discussion indicate that the measurement scale is divided into four hierarchical levels: nominal, ordinal, interval, and ratio, where each level determines the data structure and the type of statistical analysis that can be applied. In addition, this article describes attitude measurement instruments such as the Likert Scale, Guttman Scale, Semantic Differential Scale, and Rating Scale. Regarding sampling techniques, the discussion is divided into probability sampling (simple random, systematic, stratified, and area) for statistical objectivity, and non-probability sampling (purposive, convenience, snowball, quota, and saturation) for in-depth phenomena in a specific population. This article is expected to be a reference for researchers in maintaining the integrity, validity, and credibility of research findings in the field of education.